Johnson's map of New York and the adjacent cities. - Johnson and Ward (Johnson and Ward, 1864)
Map shows the street names, wards, railroads, military installations, ferry routes, parks, and some buildings for New York City and parts of Brooklyn, Jersey City, and Hoboken. Also shows names of buildings on Blackwells Island. Inset: Continuation of the City & County of New York on a reduced scale. Scale [ca. 1:20,300].